Clinical characteristics and outcome of patients aged over 80 years with covid-19. Issue 8 (26th February 2021) - Capdevila-Reniu, Aina; Pellice, Martina; Prieto-González, Sergio; Ventosa, Helena; Ladino, Andrea; Naval, Jose; Rodriguez-Nuñez, Olga; César Milisenda, Jose; Moreno-Lozano, Pedro Juan; Soriano, Alex; Bosch, Xavier; López-Soto, Alfonso
Abstract : Abstract: To investigate the clinical characteristics and outcome of octogenarians with covid-19. This is a observational, retrospective, descriptive study. Consecutive patients aged >80 years who were admitted for covid-19 pneumonia during a 6 weeks period (March 20–April 30, 2020). Illness severity on admission was classified according to World Health Organization (WHO) criteria: mild, moderate, severe, and critical. Data collected included demographics, presenting symptoms, radiological and laboratory findings, comorbidities, functional status, treatment, and clinical outcome. There were 159 patients (52.2% women) with a median age of 85.99 (IQR: 80–98). The median Barthel index was 90 (40–100) and Charlson index was 5 (5–6). Most common presenting symptoms were fever, dyspnea, and cough. Patients had mild (8.2%), moderate (52.2%), or severe (39.6%) illness according to WHO criteria. A bilateral pulmonary involvement was seen in 86% of patients. Laboratory analysis revealed increased serum concentrations of inflammatory parameters (C-reactive protein, ferritin, lactate dehydrogenase, and D-dimer) with an abnormal lymphocyte count [0.88 × 10 9 /L (0.5)]. Treatments included corticosteroids in 37%, and biological therapies in 17.6%. Fifty three (33.3%) patients died during hospitalization, with a median time from admission to death of 3 (IQR 1–6) days. Mortality was higher in men (55%). Deceased patients had a significantly higher frequency of dyspnea, increased inflammatory parameters, and illness severity compared to survivors. One-third of octogenarians with covid-19 died during hospitalization and most had bilateral lung involvement. A further knowledge of the characteristics and outcome of this population may assist clinicians in the decision-making process in these patients.